Cluster Analysis of Visitor Perceptions Toward Indonesia’s Tourism Marketing Mix in Dubai - Haq, Ramiz Ansharil (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2025)
This study examines the impressions of 174 visitors to the Wonderful Indonesia booth at Arabian Travel Market (ATM) Dubai 2024 regarding the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) with a Likert scale questionnaire ranging from 1 to 5. The k-means analysis technique categorizes respondents into three clusters according on perceptual similarities,with Cluster 2 (62.64%) representing the most favourable group and Cluster 3 (20.11%) the most critical. ANOVA results indicate significant differences (p<0.001) among clusters, particularly in Price (F=116.144) and Process (F=96.267), which are the primary distinguishing factors. The examination of Euclidean distance indicates that the greatest gap between Clusters 2 and 3 is 4.592 signifying significant polarization of perceptions. The results demonstrate that Product achieved the greatest score (Mean=4.45) whereas Process and Price represented the primary deficiencies in Cluster 3. The strategic implications underscore the necessity for marketing distinction through segmentation particularly by enhancing service protocols and modifying pricing structures. This study offers an empirical foundation for formulating Indonesian tourism strategies in the global market.